Mathematical modelling of factory fire - Luqman Hakim Roslee (Nanyang Technological University, 2020)
This project investigates the causes and conditions for a pile of sawdust placed on top of a hot press to catch fire. The report covers the derivation of equations that are involved in the causes and conditions, and also the utilization of these equations to determine the temperature distribution of the sawdust. Free body diagrams, calculus, heat conduction equations and graphical methods are being used to obtain the information that is necessary to determine if spontaneous ignition will occur for the sawdust on top of the hot press.